Influence of Microscopic Effects on the Static Tensile Strength of Gray Cast Iron HT200 Specimens - L. Fan; H. B. Hu; X. S. Tang; J. J. He; W. Chen (Advances in Materials Science and Engineering)
Gray cast iron HT200 material is a kind of pearlitic gray cast iron. Flake graphite in the gray cast iron greatly destroys the integrity of the matrix and affect the static strength. The influence of microscopic effects on the tensile static strength of gray cast iron HT200 specimens is investigated. The microstructures are observed by the scanning electron microscope. The failure tests are done under the static loads for the cylinder specimens of gray cast iron HT200. Then, an energy density zone (EDZ) model is applied to the simulation of the fracture process of the specimens. The energy density zone model is a macro/micro-trans-scale crack growth model that can depict a fracture process from an initial microdefect at the microscale to the final break at the macroscale. Three scale transitional functions as well as the size of the initial microdefect in the model represent the microscopic effects in a fracture process. Three scale transitional functions are speculated in view of the physical failure mechanisms. Two other material parameters in the model are determined from the test data. Thereby, the fracture process of gray cast iron specimens is numerically simulated, and the static strength values are calculated. The calculated values of static strength of gray cast iron specimens are identical to the test values. It is seen that the energy density zone model can accurately describe a fracture process of brittle materials like gray cast iron. In addition, the calculated results show that the microscopic effects did affect the static strength of gray cast material.